Dental caries and the associated factors influencing it in tribal, suburban and urban school children of Tamil Nadu, India: a cross sectional study - J. Baby John; Sharath Asokan; Aswanth KP; P.R. Geetha Priya; A.K. Shanmugaavel (SAGE Publishing, 2015)
Background. The study was planned to assess the prevalence of dental caries among tribal, suburban and urban children of Tiruchengode and Erode of Tamil Nadu state, India. The objective of the study was to assess the association of dental caries with family background, dental service availability, transportation and knowledge on preventive dental measures among these three groups. Design and methods. Cross-sectional study. A total of 1028 school children in the age range of 9-12 years from various government schools located in Palamalai and Kolli Hills (tribal), Tiruchengode (suburban) and Erode (urban), Tamil Nadu, were included in the study. Decayed, filled, and missing teeth (DMFT), decayed and filled teeth (dft) and Significant Caries Index were recorded. A specially prepared questionnaire was used to record all the data regarding oral hygiene practices, socioeconomic background, dental treatment availability, parent's education level were used for the study. ANOVA t-test and post hoc test were used for comparing quantitative variables between the 3 subgroups. Results. The tribal school children had 89.3% caries prevalence, where as it was 77% in suburban and 55% in urban school children. The mean DMFT score among tribal, suburban and urban school children were statistically significant different (P=0.001) between the three groups. There was a highly significant difference (P=0.001) in the mean DMFT score based on brushing frequency. There was a statistically significant difference (P=0.018) in the mean DMFT scores in the urban group based on the mothers education status. There were no statistically significant differences in the mean DMFT scores based on the presence or absence of television in their house and the parents' income. Conclusions. Oral hygiene practices, dietary habits and access to dental care services played an important role in prevalence of dental caries. It was observed that the socioeconomic status, parents' educational status and mass media influenced the oral health of these children but without a significant contribution.